Epicenter why the current rumblings in the Middle East will change your future - Rosenberg, Joel C. 1967- (OMF Literature, 2008)
Based on interviews with political, military, intelligence, business, and religious leaders in Israel, Iran, Iraq, and Russia; newly declassified documents from the CIA, Pentagon and White House; an exclusive poll of American attitudes toward biblical prophecy, Israel, and current events; and his own interpretation of biblical prophecy, Rosenberg presents ten "future headlines" for the Middle East and the world.